FORECASTING PRODUKSI PERIKANAN LAUT YANG DIJUAL DI TPI (TON) DENGAN METODE SINGLE EXPONENTIAL SMOOTHING - Ivana Larasati Putri Navalina; Nur Indah Riwajanti; Sugeng Sulistyono; Ludfi Djajanto (Media Mahardhika, 2020)
The purpose of this study was to determine the results of forecasting the production of fish sold at TPI in 2018-2020. This is expected to help the government in the formulation of plans and strategies related to the production of marine fish to increase the GRDP of fisheries in Java (regional level) and fisheries GDP in Indonesia (national level) and to contribute in the field of information and macroeconomics. This research used descriptive quantitative research and used data obtained through the official website of the Central Statistics Agency. This study used the Single Exponential Smoothing method. The results of this study have shown that the areas with the lowest sea fish production are in the DI Yogyakarta area, so the government must devise a strategy to maximize fish production in order to increase the PRDB contribution in Yogyakarta.